2016
DOI: 10.1007/s13762-016-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and post-treatments of ordered mesoporous carbons (OMC) for resorcinol removal

Abstract: In this investigation, acrylic acid was used as a carbon precursor and SBA-15 as a mesoporous template to synthesize the ordered mesoporous carbons (OMC). Different ratios of SBA-15 to acrylic acid were evaluated to improve the OMCs adsorption capacity. It was found that the optimal ratio of SBA-15 to acrylic acid is 3:1. In the post-treatment study, four methods (NaOH, urea, NH 3 H 2 O, and AlCl 3 ) were explored to investigate their influences on resorcinol removal. Results showed the ammonium hydroxide-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The carbonyl (C=O) band appeared at 1740 cm −1 in PVDF etched OMC shows strong absorption compared to HF and NaOH etched OMCs. The strong band at 1580 cm −1 in NaOH etched OMC corresponds to C=C bonds ,. It may due to the large exposure of defect sites which partially converted to oxygen containing functional groups like COOH and OH during etching process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbonyl (C=O) band appeared at 1740 cm −1 in PVDF etched OMC shows strong absorption compared to HF and NaOH etched OMCs. The strong band at 1580 cm −1 in NaOH etched OMC corresponds to C=C bonds ,. It may due to the large exposure of defect sites which partially converted to oxygen containing functional groups like COOH and OH during etching process.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, the absorption bands at 2900 and ∼1134 cm −1 are assigned to C−H and C−O stretching modes respectively. The lower wavenumber, below 1000 cm −1 , assigned to the C−H deformation out plane bending vibration . Importantly, we observed that high intense strong absorption bands in NaOH etched OMC.…”
Section: Resultsmentioning
confidence: 99%
“…It is preferred that adsorbents have a well‐defined mesoporous structure (2–50 nm) for the efficient removal of organic pollutants. Ordered mesoporous carbons (OMCs), a new member of the carbonaceous family, have been able to attract substantial attention because of its distinct attributes, such as high BET surface area, narrow pore size distribution, well defined ordered structure, large pore volume, and thermal stability , which promoted research development for the modification of OMCs with tunable pore sizes and improved surface chemistry , making them more suitable candidate for applications such as adsorption , catalyst support , CO 2 capture , and hydrogen storage . Traditionally nanocasting technique is employed for the synthesis of OMCs .…”
Section: Introductionmentioning
confidence: 99%